Mitigating ipatasertib‐induced glucose increase through dose and meal timing modifications. Issue 12 (16th November 2022) - Sutaria, Dhruvitkumar S.; Agarwal, Priya; Huang, Kuan‐Chieh; Miles, Dale R.; Rotmensch, Jacob; Hinton, Heather; Gallo, Jorge Daniel; Rasuo, Grozdana; Sane, Rucha S.
Abstract: Ipatasertib, an AKT inhibitor, in combination with prednisone and abiraterone, is under evaluation for the treatment of metastatic castration‐resistant prostate cancer (mCRPC). Hyperglycemia is an on‐target effect of ipatasertib. An open‐label, single‐arm, single‐sequence, signal‐seeking study ( n  = 25 mCRPC patients) was conducted to evaluate the glucose changes across four different treatment periods: ipatasertib alone, ipatasertib‐prednisone combination, ipatasertib‐prednisone‐abiraterone combination (morning dose), and ipatasertib‐prednisone‐abiraterone combination (evening dose). Continuous glucose monitoring (CGM) was used in this study to compare the dynamic glucose changes across the different treatment periods. Four key parameters: average glucose, peak glucose and % time in range (70–180 and >180 mg/dl) were evaluated for this comparison. Ipatasertib‐prednisone‐abiraterone combination when administered in the morning after an overnight fast significantly increased average glucose, peak glucose and % time in range >180 mg/dl compared to ipatasertib monotherapy. Ipatasertib, when co‐administered with abiraterone, increased ipatasertib and M1 (G‐037720) metabolite exposures by approximately 1.5‐ and 2.2‐fold, respectively. Exposure–response analysis results show that increased exposures of ipatasertib in combination with abiraterone are associated with increased glucose levels. When ipatasertib‐prednisone‐abiraterone combination was administered as an evening dose compared to a morning dose, lowered peak glucose and improved % time in range was observed. The results from this study suggest that dosing ipatasertib after an evening meal followed by overnight fasting can be an effective strategy for managing increased glucose levels.